Factors closing the attitude-behavior gap for sustainable consumption in the fashion industry : A study of Finnish consumers - Heiniemi, Henrika (My University, 2024)
The issue of climate change and environmental degradation has led to a growing concern for the world’s resources. Current consumption levels exceed the earth’s capacity, yet the rate of consumption continues to increase, accompanied by a corresponding rise in the negative environmental and social consequences. The fashion industry is a significant contributor to environmental and social problems on a global scale. This is largely due to the emergence of a new business model, fast fashion, which refers to mass-produced and low-cost clothing. Consequently, the rate of fashion consumption is at an all-time high, with clothes being purchased and discarded at an alarming rate. This has created a need for more sustainable practices. Despite the increased concern about sustainability that has led consumers to adopt more positive attitudes towards it, consumers do not consume fashion sustainably. This attitude-behavior gap in the field of sustainable fashion consumption has been widely acknowledged. Researchers have proposed that by identifying the underlying causes of the gap, it may be possible to encourage more sustainable purchasing behaviors. Although prior research delves into this research topic, it provides a very limited understanding of factors closing the attitude-behavior gap in purchasing sustainable fashion products. Therefore, the objective of this research is to investigate the factors that contribute to closing the consumers’ attitude-behavior gap for sustainable consumption in the fashion industry. Based on a literature review, the following factors have been identified as the most significant barriers to sustainable consumption: a lack of awareness, a lack of knowledge about sustainability and misconceptions, high prices, low availability and a negative image of sustainable fashion, and a lack of trust and skepticism. In order to overcome these barriers, six factors have been identified that could potentially facilitate sustainable consumption. Based on these findings, six hypotheses have been formulated. The developed hypotheses have been tested by collecting quantitative data from 156 Finnish customers. Empirical data analysis based on multiple regression analysis has supported five out of six hypotheses. The findings suggest that the five factors contributing to closing the attitude-behavior gap in buying sustainable fashion products are: awareness of the negative effects of consumption, sustainable fashion knowledge, perceived value of sustainable clothing, availability of sustainable clothing, and perceived customer effectiveness. The findings indicate that fashion companies can motivate consumers to consume sustainable fashion by including these factors in their communication and marketing efforts. It should be a shared effort where companies provide more sustainable fashion options and consumers willingly consume them.

Ilmastonmuutos ja ympäristöongelmat aiheuttavat kasvavaa huolta maailman luonnonvarojen riittävyydestä. Tämänhetkinen kulutustaso ylittää jo nykyisellään maapallon kapasiteetin, mutta kulukseen määrä ja sen aiheuttamat negatiiviset ympäristölliset ja sosiaaliset haitat jatkavat kasvuaan. Muotiteollisuus on poikkeuksellisen suuri ympäristö- ja sosiaalisten ongelmien aiheuttaja globaalilla kentällä. Tämä johtuu suurelta osin uuden liiketoimintamallin, pikamuodin suosiosta alalla. Pikamuoti-liiketoimintamallin seurauksena muodin kulutus on ennätyksellinen nopeaa, kun halpoja ja massatuotettuja vaatteita ostetaan ja niistä hankkiudutaan eroon hälyttävää tahtia. Tämä on luonut tarpeen kestävämmille ja vastuullisille käytännöille. Huolimatta siitä, että huoli kestävyydestä on saanut kuluttajat suhtautumaan vastuullisuuden käsitteeseen myönteisemmin, kuluttajat eivät silti kuluta muotia kestävällä tavalla. Tämä asenteiden ja käyttäytymisen välinen kuilu on tunnistettu laajalti aikaisemmissa kestävän muodin tutkimuksissa. Tutkijat ovat ehdottaneet, että tunnistamalla kuilun taustalla olevia syitä, jotka mahdollisesti selittävät sen, mikseivät kuluttajat tee vastuullisia kulutuspäätöksiä, kuluttajia voidaan kannustaa kestävämpään ostokäyttäytymiseen. Vaikka aiemmissa tutkimuksissa aiheeseen on perehdytty laajalti, ne tarjoavat silti vain hyvin rajallisen käsityksen tekijöistä, jotka auttavat kaventamaan tätä asenteiden ja käyttäytymisen välistä kuilua ja edistävät kestävien muotituotteiden kulutusta. Tästä syystä tämän tutkimuksen tavoitteena on tutkia tekijöitä, jotka edistävät kuluttajien asenteiden ja käyttäytymisen välisen kuilun kuromista umpeen edistämällä kestävää muodin kulutusta. Kirjallisuuskatsauksen perusteella on todettu viisi merkittävintä estettä, jotka saattavat aiheuttaa kuilun asenteiden ja käytöksen välille ja estää kuluttajia tekemästä vastuullisia valintoja. Nämä tekijät ovat tietoisuuden puute, tietämättömyys kestävyydestä ja väärinkäsitykset, korkeat hinnat, heikko saatavuus ja kielteinen kuva sekä luottamuksen puute ja skeptisyys. Näiden tulosten perusteella tälle tutkimukselle on kehitetty kuusi hypoteesia. Kehitettyjä hypoteeseja on testattu keräämällä kvantitatiivista tietoa 156 suomalaiselta kuluttajalta. Moninkertaiseen regressioanalyysiin perustuva empiirinen analyysi on tukenut viittä kuudesta hypoteesista. Tulosten pohjalta voidaan todeta, että viisi tekijää, jotka positiivisesti edistävät vastuullisen muodin ostamista ja kaventavat asenteiden ja käyttäytymisen välistä kuilua ovat seuraavat: tietoisuus kulutuksen kielteisistä vaikutuksista, kestävän muodin tuntemus, kestävän muodin koettu arvo, kestävien vaatteiden saatavuus ja koettu kuluttajatehokkuus. Tulokset osoittavat, että muotialan yrityksen voivat motivoida kuluttajia kuluttamaan kestävää muotia sisällyttämällä näitä tekijöitä viestintä- ja markkinointitoimiinsa. Kyseessä on oltava yhteinen ponnistus, jossa yritykset tarjoavat kestävämpiä vaihtoehtoja muodille ja kuluttajat kuluttavat niitä mielellään.
Keywords: sustainable consumption; consumer behaviour; fashion sector; sustainable development; fashion; clothing industry; consumption; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business